2020
DOI: 10.1126/science.abc8530
|View full text |Cite
|
Sign up to set email alerts
|

Metasurface-driven OLED displays beyond 10,000 pixels per inch

Abstract: Optical metasurfaces are starting to find their way into integrated devices, where they can enhance and control the emission, modulation, dynamic shaping, and detection of light waves. In this study, we show that the architecture of organic light-emitting diode (OLED) displays can be completely reenvisioned through the introduction of nanopatterned metasurface mirrors. In the resulting meta-OLED displays, different metasurface patterns define red, green, and blue pixels and ensure optimized extraction of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
159
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(159 citation statements)
references
References 29 publications
0
159
0
Order By: Relevance
“…demonstrated that a metasurface mirror can be integrated into the OLED microcavity structure to enhance the OLED configuration. [ 153 ] Therefore, the combination of OLED technology with wide‐range dynamic structural colors—which substitutes the conventional RGB pixels with a single pixel and dynamically covers the entire visible range—has the potential to further improve display performances in terms of saturation, resolution, efficiency, and stability.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that a metasurface mirror can be integrated into the OLED microcavity structure to enhance the OLED configuration. [ 153 ] Therefore, the combination of OLED technology with wide‐range dynamic structural colors—which substitutes the conventional RGB pixels with a single pixel and dynamically covers the entire visible range—has the potential to further improve display performances in terms of saturation, resolution, efficiency, and stability.…”
Section: Discussionmentioning
confidence: 99%
“…The power saving (unit: %) between red, green, and blue (RGB) micro-light-emitting diode (μLED) displays with different chip sizes and uniform chip size than 10,000 PPI has been proposed, 159 the spatially distributed metasurfaces with different reflection phase is designed in the microcavity to tune the cavity resonances in RGB subpixels. In parallel, μLED microdisplays with PPI > 5000 have also been developed.…”
Section: Resolution Densitymentioning
confidence: 99%
“…Metal nanostructures in various morphologies, such as nanohole arrays, 130,131 and nanopixels based on metallic films, 129,132 have been widely investigated. The principles of metallic nanoantenna, 41,50,133,134 metallic GMR grating, 135 and disordered plasmonic systems 67 are widely investigated. H. F. Ghaemi et al 136 demonstrated the extraordinary optical transmissions through periodic subwavelength hole arrays in optically thick metallic films.…”
Section: Review Llmentioning
confidence: 99%